24 Years-Old Adolescent WITH Internet Addiction Disorder Through A Family Medicine Approach - Emilius, Denny; Soeryani, R. Wianti; Lumbuun, Nicolaski (CV. Jasa Sukses Abadi, 2024)
Internet Addiction Disorder (IAD) is an increasing public health problem among adolescents. As a branch of medical science that plays an important role in handling public health problems, family medicine has a unique perspective in understanding and seeking solutions to the problem of IAD in adolescents. This case report aims to explain the family medicine approach in managing IAD in adolescents, including the identification of risk factors, holistic interventions, and the role of family physicians in preventive, curative, and rehabilitative efforts. The case study of a 24-year-old adolescent with IAD, using a family medicine approach, obtained an in-depth understanding of the psychological, social, and physiological dynamics underlying IAD in adolescents is key for family doctors in designing effective interventions. A family medicine approach that focuses on the unique needs and context of each adolescent patient can provide more comprehensive solutions. Family physicians play an important role in early screening, education, referral to mental health services, and collaboration with parents, schools, and communities. Preventive efforts are also made through the promotion of healthy internet use, development of self-regulation skills, and family/community empowerment. The family medicine approach in managing adolescent IAD places doctors as agents of change who focus on promotive, preventive, curative, and rehabilitative efforts. Collaboration between the government, professional associations, and other stakeholders is needed to develop an effective framework to prevent and address IAD in adolescents.